Use of a Full Factorial Design to Study the Relationship between Water Absorption and Porosity of GP and BW Mortar Activated - Nadia Tebbal; Mekki Maza; Zine El Abidine Rahmouni (Advances in Civil Engineering)
The alkali-activated materials prepared by activation of glass powder (GP) and brick waste (BW) on the porosity and absorption of geopolymer paste by alkaline solution (alkali + water glass) were investigated. The effect of the combination of GP and BW on the porosity and absorption of the prepared geopolymer paste was monitored and evaluated by both laboratory and analytical methods. In this paper, three mortars were made with two sources of geopolymer containing 100% BW and 100% GP and blended with 90% GP and 10% BW replacements by mass. The compressive strength, porosity, and absorption of alkali-activated mortar were concurrently examined. Furthermore, the laboratory results obtained were estimated by the general full factorial design method. Finally, the analysis of variance was performed using the test results to analyze the importance of the effect factors and their interactions on the selected responses. The results concluded that mortar activated combined with 10% BW and 90% GP could be utilized in the industry of construction with minimum pollution problems and environment-friendly building materials, with the effect variables significantly affecting the responses.